PERAN PESANTREN DALAM MENANAMKAN NILAI KEBERKAHAN PADA GENERASI MUDA - Nadia Nabila; Muhammad Husni (KAMPUS AKADEMIK PUBLISING, 2026)
Pesantren, as Islamic educational institutions, have a strategic mission in building the character and faith of young generations. They function not only as educational centers amid the challenges of globalization and moral crisis, but also as institutions for instilling virtuous values. Pesantren focus on the formation of moral character, spiritual strength, and a meaningful life orientation. This study aims to examine how pesantren play a significant role in instilling the value of barakah (blessing) in young generations and to develop a conceptual model of its internalization process. This study employs a qualitative approach with a library research design. Data were obtained from books, scholarly journals, and previous studies related to barakah, pesantren, and character education. Data analysis was conducted through content analysis using a thematic approach to identify ideas, patterns, and the ways pesantren contribute to the cultivation of barakah values. The findings indicate that pesantren instill the value of barakah through a distinctive educational system that includes the central role of the kiai, scholarly and spiritual traditions, a culture of discipline, and a religious and collective environment. The internalization of values occurs through role modeling, habituation, and students’ lived experiences, so that barakah is not only understood theoretically but is also embodied as a life orientation. This process contributes to the formation of young generations with strong moral character, spiritual depth, moral resilience, and a meaningful and beneficial life orientation. This study proposes a model of the pesantren’s role in instilling the value of barakah through the following sequence: Islamic literature → pesantren system → internalization process → character of young generations. This model affirms that pesantren can serve as a foundation for character and spiritual education in building a morally grounded young generation.